Penerapan Psychological First Aid berbasis Crisis Emergency Theory dengan Kesiapan Stigma Sosial Penderita Kusta Wilayah Pesisir Provinsi Maluku - Idham Soamole; Windarti Rumaolat; Wiwi Rumaolat (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2026)
Leprosy causes permanent physical disability and triggers negative perceptions resulting in social and economic disparities for sufferers. Psychological First Aid (PFA) is a concept that focuses on crisis conditions. The aim of this research is to determine the relationship between psychological first aid based on crisis emergency theory and readiness for social stigma.  This research method is analytical descriptive with a cross sectional approach, sample size of 123 respondents, cluster sampling technique. The variables studied are the independent variables, namely individual factors, psychological factors, external factors, mental health crisis emergencies, and psychological first aid based on crisis emergencies theory. The dependent variable is social stigma. The research instrument used a questionnaire. Data analysis in this study used the PLS approach. The research results showed that there was no relationship between individual internal factors and The Crisis Mental Health Emergency (CMHE) p-value 0,730, there was a relationship between individual psychological factors and The CMHE p-value 0,000, there was a relationship between individual external factors and The CMHE p-value 0,030, there was a relationship between The CMHE and PFA p-value 0,000, there was no relationship between The CMHE and Negative Stigma in Society p-value 0,330 and There was a relationship between PFA and stigma. negative society p-value 0,000. The stronger the external factors that support it, the potential for a mental health crisis decreases and the more effective psychological first aid is, the lower the negative stigma of society towards mental health issues.